2021
DOI: 10.1001/jamanetworkopen.2021.20929
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of a High-Dose vs Standard-Dose Hepatitis B Revaccination Schedule Among Patients With HIV

Abstract: Key Points Question What is the efficacy of a high-dose vaccine schedule compared with standard dosage for hepatitis B virus (HBV) revaccination in patients living with HIV? Findings In this randomized clinical trial including 107 adults at a single HIV and hepatology clinic in Chile, 72% of patients receiving a high dose of HBV vaccine achieved serological response as compared with 51% in the standard-dose group. Higher and longer-lasting hepatitis B surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…For patients undergoing dialysis therapy, alternative strategies include the use of adjuvants, additional vaccination cycles, different vaccine formulations, greater number and concentration of doses, greater frequency of doses, dual vaccination, alternative administration routes, and/or use of booster vaccines[ 67 , 72 , 84 - 86 ]. On the other hand, for HIV-infected individuals with negative or < 10 mIU/mL anti-HBs levels after a primary vaccine series, a second HBV vaccine series using larger or additional doses is recommended[ 71 , 87 ]. Furthermore, revaccination should be attempted after HIV viral load suppression and CD4 cell count improvement[ 83 ].…”
Section: Management Of Special Populationsmentioning
confidence: 99%
“…For patients undergoing dialysis therapy, alternative strategies include the use of adjuvants, additional vaccination cycles, different vaccine formulations, greater number and concentration of doses, greater frequency of doses, dual vaccination, alternative administration routes, and/or use of booster vaccines[ 67 , 72 , 84 - 86 ]. On the other hand, for HIV-infected individuals with negative or < 10 mIU/mL anti-HBs levels after a primary vaccine series, a second HBV vaccine series using larger or additional doses is recommended[ 71 , 87 ]. Furthermore, revaccination should be attempted after HIV viral load suppression and CD4 cell count improvement[ 83 ].…”
Section: Management Of Special Populationsmentioning
confidence: 99%
“…Age is an important factor for reduced immunogenicity and vaccine-induced protection due to immunosenescence ( 30 ). Higher antigen doses of influenza or hepatitis B vaccines enable to increase vaccine responses in older adults or patients at risk for vaccine non response ( 31 , 32 ). Therefore, it can be speculated that the higher dose of the mRNA-1273 may overcome an age-related decrease in immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients who received a single dose and had anti-HBs > 100 was 46/91 (50.5%), which is at considerably low level compared to the healthy population. In a prospective randomized study, it was shown that the serological response rate of those who received the high dose was 72%, while the rate of those who received the standard dose was 50% (17).…”
Section: Discussionmentioning
confidence: 99%